Efficacy of population‐wide diabetes and obesity prevention programs: An overview of systematic reviews on proximal, intermediate, and distal outcomes and a meta‐analysis of impact on BMI. (30th April 2019) - Roberts, Samantha; Pilard, Louis; Chen, Junqiao; Hirst, Jennifer; Rutter, Harry; Greenhalgh, Trisha
Summary: We conducted an overview of systematic reviews and a meta‐analysis of the impact on body mass index (BMI) of primary studies of population‐wide obesity and diabetes prevention programs, in order to evaluate their efficacy. We searched eight databases for reviews of population‐level programs reporting effect on diet, physical activity, BMI, or prevalence of obesity/overweight or type 2 diabetes mellitus (T2DM). Meta‐analysis of primary studies within reviews reporting effect on BMI. Interventions were categorized using ANGELO framework and quality assessment using AMSTAR. Fifty‐three systematic reviews were included. Primary studies were largely natural experiments or cross‐sectional studies of national data. Increased price of sugar‐sweetened beverages (SSBs) and fast food, decreased price of fruit and vegetables, food labelling, and grocery store interventions were associated with positive effects on diet. Park and playground renovations and point‐of‐choice prompts to increase stair use were associated with positive effects on physical activity. Increased price of SSBs, menu labelling, grocery store interventions, and multicomponent interventions were associated with small reductions in BMI. There was insufficient evidence of impact of any interventions on the prevalence of overweight, obesity, or T2DM. We have identified a promising suite of population‐wide actions to improve diet, increase physical activity, and reduce BMI. Impact on subsequent incidence of T2DM remains speculative.